2014
DOI: 10.1038/tp.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict burnout severity from empathy-related brain activity?

Abstract: Empathy cultivates deeper interpersonal relationships and is important for socialization. However, frequent exposure to emotionally-demanding situations may put people at risk for burnout. Burnout has become a pervasive problem among medical professionals because occupational burnout may be highly sensitive to empathy levels. To better understand empathy-induced burnout among medical professionals, exploring the relationship between burnout severity and strength of empathy-related brain activity may be key. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 54 publications
3
83
1
8
Order By: Relevance
“…Chronic ‘sharing of an emotional state’ with an offspring can lead to maladaptive changes in brain processing and emotional burnout, as high levels of empathy not only provides an advantage for recognizing others emotions, but is also associated with a bias toward negative emotions with a higher risk for empathic distress (Chikovani et al, 2015). Emotional burnout has been linked to decreased activation in the temporoparietal junction and the anterior insula coupled with a decreased ability to identify an internal emotional state (alexithymia) (Tei et al, 2014). These and other influences may alter the empathetic response in parents (Preston, 2013; Shirtcliff et al, 2009; Soria Bauser et al, 2012; Thakkar et al, 2009) including stress reactivity (Obradovic et al, 2010; Rodrigues et al, 2009; Shirtcliff et al, 2009).…”
Section: The Maladaptive Feedback Loop Leading To Altered Brain Stmentioning
confidence: 99%
“…Chronic ‘sharing of an emotional state’ with an offspring can lead to maladaptive changes in brain processing and emotional burnout, as high levels of empathy not only provides an advantage for recognizing others emotions, but is also associated with a bias toward negative emotions with a higher risk for empathic distress (Chikovani et al, 2015). Emotional burnout has been linked to decreased activation in the temporoparietal junction and the anterior insula coupled with a decreased ability to identify an internal emotional state (alexithymia) (Tei et al, 2014). These and other influences may alter the empathetic response in parents (Preston, 2013; Shirtcliff et al, 2009; Soria Bauser et al, 2012; Thakkar et al, 2009) including stress reactivity (Obradovic et al, 2010; Rodrigues et al, 2009; Shirtcliff et al, 2009).…”
Section: The Maladaptive Feedback Loop Leading To Altered Brain Stmentioning
confidence: 99%
“…This last point, together with the findings of Tei et al. () who showed more burnout in nurses, raises an important issue that needs to be taken into consideration in the training of nurses working in ICUs. Sharing pain vicariously and repetitively does come with some cost and while experience may attenuate part of the affective response, such change might occur at the expense of nurses’ mental health.…”
Section: Discussionmentioning
confidence: 84%
“…This adds to the evidence that paediatric nurses’ chronic exposure to infant pain leads to a habituation effect in the IFG/AI response to this pain. Of relevance, a previous study (Tei et al., ) has shown that activation in this region in response to vicarious pain was lower in nurses with higher symptoms of burnout.…”
Section: Discussionmentioning
confidence: 88%
“…In support of this finding, several studies have indicated that higher empathy may not always be associated with positive outcomes. For instance, although empathy is considered a central factor in establishing a superior professional-client partnership in nursing (Augusto-Landa and López-Zafra, 2010), excessive empathy was a risk factor for compassion fatigue (Wentzel and Brysiewicz, 2014), burnout (Tei et al, 2014) and depression (Schieman and Turner, 2001). Moreover, a similar finding has also been reported for altruism (Altun, 2002).…”
Section: The Beneficial Profiles Of Eimentioning
confidence: 77%